High density lipoprotein as prognostic indicator in patient with diabetic foot - Singara, Arie Rafael; Rasjad, Chaeruddin; Latief, Jufri; Mustari, Nasser; Bausat, Arman (International Journal of Research in Medical Sciences, 2020)
Background: Diabetic is a chronic metabolic disease with vascular disorder and HDL (High Density Lipoprotein) is a vascular protector acting agent. One of the most difficult complication of diabetics are diabetic foot with often lead to an amputation due to vascular disorder. Objective of this study aims to determine the relationship of HDL levels with diabetic foot severity by comparing HDL levels in each diabetic foot grade according to the Wagner classification. Methods: This is a cross sectional study, with new inpatient and outpatient with diabetic foot ulcer that never received therapy in Wahidin Sudirohusodo Hospital as a study population in April 2018 to June 2018 time period. Frequency distribution, Spearman’s Correlation, Anova, and Chi Square statistical analytic was done with p <0.05 considered as significant. Results: HDL level was wound highest in Grade I and lowest in Grade IV and V. HDL level comparison according to Wagner comparison shows significant difference, p<0.001. Conclusions: There were a negative correlation as an analysis results shows between HDL level and Wagner classification, whereas the lower HDL level, the higher diabetic foot grade and HDL can be used as a prognosis predictor and planning therapy.